Perbedaan Keanekaragaman Jenis Semut (Hymenoptera: Formicidae) Pada Dua Tipe Habitat di Taman Wisata Alam Lembah Harau - Anggun Rafila Putri; Fitra arya Dwi Nugraha; Reki Kardiman; Rijal Satria (Jurnal Biologi Universitas Andalas, 2023)
A total of 11 species belonging to 10 genera, 3 subfamilies with a total of 133 individual litter ants were collected at the Lembah Harau Nature Tourism Park. The results showed that the ecosystem of the Lembah Harau Natural Tourism Park tends to be stable. This is indicated by the index of ant diversity in the natural habitat of 0.98 which is low, while in the disturbed habitat it is 1.83, which is classified as moderate. as well as the dominance index in natural and disturbed habitats, namely 0.56 and 0.18 so that it can be concluded that no species dominates in these two habitats